Blood Pressure Variability Predicts Poor In-Hospital Outcome in Spontaneous Intracerebral Hemorrhage. Issue 8 (August 2019) - Divani, Afshin A.; Liu, Xi; Di Napoli, Mario; Lattanzi, Simona; Ziai, Wendy; James, Michael L.; Jafarli, Alibay; Jafari, Mostafa; Saver, Jeffrey L.; Hemphill, J. Claude; Vespa, Paul M.; Mayer, Stephan A.; et al.
Abstract : Background and Purpose—: There is increasing evidence that higher systolic blood pressure variability (SBPV) may be associated with poor outcome in patients with intracerebral hemorrhage (ICH). We explored the association between SBPV and in-hospital ICH outcome. Methods—: We collected 10-years of consecutive data of spontaneous ICH patients at 2 healthcare systems. Demographics, medical history, laboratory tests, computed tomography scan data, in-hospital treatments, and neurological and functional assessments were recorded. Blood pressure recordings were extracted up to 24 hours postadmission. SBPV was measured using SD, coefficient of variation, successive variation (SV), range and 1 novel index termed functional SV. The effects of SBPV on the functional outcome at discharge were evaluated by multivariate logistic and ordinal regression analyses for dichotomous and trichotomous modified Rankin Scale categorizations, respectively. In secondary analyses, associations between SBPV, history of hypertension, and hematoma expansion were explored. Results—: The analysis included 762 subjects. All 5 SBPV indices were significantly associated with the probability of unfavorable outcome (modified Rankin Scale score, 4–6) in logistic models. In ordinal models, SD, coefficient of variation, range, and functional SV were found to have a significant effect on the probabilities of poor (modified Rankin Scale score, 3–4) and severe/death (modified Rankin Scale score, 5–6) outcomes. Normotensive patients had significantly lower mean SBPV compared with the untreated-hypertension cohort for all SBPV indices and compared with treated-hypertension patients for 3 out of 5 SBPV indices. Lower mean SBPV of treated-hypertension subjects compared with untreated-hypertension subjects was only detected in the SV and functional SV indices ( P =0.045). None of the SBPV indices were significantly associated with the probability of hematoma expansion. Conclusions—: Higher SBPV in the first 24 hours of admission was associated with unfavorable in-hospital outcome among ICH patients. Further prospective studies are warranted to understand any cause-effect relationship and whether controlling for SBPV may improve the ICH outcome. Abstract : Supplemental Digital Content is available in the text.